TELISIK DETERMINAN NILAI PERUSAHAAN - Nur Rokhim; Nirsetyo Wahdi; Aprih Santoso (BBM (Buletin Bisnis & Manajemen), 2020)
The purpose of this study was to examine the effect of the variable profitability (ROA), dividend policy (DPR), solvency (DER), and company size (SIZE) on firm value (Prince to Book Value). This study uses data obtained from the annual financial statements of Manufacturing Companies listed on the Indonesia Stock Exchange in 2015-2017. The population in this research is all manufacturing companies registered in Indonesia Stock Exchange in 2015-2017 as many as 99 companies. In the purposive sampling stage, the number of samples that were suitable for use were 28 Manufacturing Companies. The data analysis method is multiple linear regression. Hypothesis testing uses t-tests to partially test variables, and F-tests. The analysis shows that profitability (ROA), dividend policy (DPR), solvency (DER) and company size (PBV) affect the firm value (PBV). Then the results of the regression analysis detected profitability (ROA), dividend policy (DPR), solvency (DER) and company size (PBV) showed an effect on firm value (PBV) of 54.8%, the remaining 45.2% influenced by other factors.